Forebrain substrates of reward and motivation - Wise, Roy A. (2005)
Electrical stimulation of the medial forebrain bundle can reward arbitrary acts or motivate biologically primitive, species-typical behaviors like feeding or copulation. The sub-systems involved in these behaviors are only partially characterized, but they appear to trans-synaptically activate the mesocorticolimbic dopamine system. Basal function of the dopamine system is essential for arousal and motor function; phasic activation of this system is rewarding and can potentiate the effectiveness of reward-predictors that guide learned behaviors. This system is phasically activated by most drugs of abuse and such activation contributes to the habit-forming actions of these drugs.